Precios y financierización: Evidencia empírica en mercado de la vivienda del Gran Santiago - Vergara Perucich, José Francisco. (Universidad de Chile, Instituto de la Vivienda, 2021)
Based on a set of data from the housing market, an empirical evaluation is developed with an econometric approach on the statistical significance of the critical aspects mentioned by the literature on the financialization of housing to assess their impact on the price for Greater Santiago between 2009 and 2019. The results indicate that there is a statistical significance between housing price formation and financial elements such as mortgage interest rates, housing loans or shares in the stock market of real estate companies, among others. These results are spatially interpreted and developed in cartographies that seek to identify the places in the city where these findings are best expressed and the neighborhoods with the greatest spatial representativeness of the variables are identified. A north-south corridor of financialization associated with hospital infrastructure, retail development and major road infrastructure investment is identified. Using the ordinary least squares method and spatial autocorrelation, the article validates the more qualitative discourses of the financialization problem and visualizes the sectors of the city where this phenomenon has the greatest impact.
Prices and financialization: Empirical evidence of housing market in Greater Santiago
Keywords: Financialisation; Ordinary least squares; Spatial autocorrelation; Precios